Effectiveness of a patient navigator on patient satisfaction in adult patients in an ambulatory care setting: a systematic review. (August 2016) - Ranaghan, Coleen; Boyle, Kathleen; Meehan, Maureen; Moustapha, Shadiatu; Fraser, Patrice; Concert, Catherine
EXECUTIVE SUMMARY: Background: One approach to overcoming healthcare system barriers and facilitating timely access to quality care and patient satisfaction is with a patient navigator. A patient navigator is a trained person who individually assists patients, families and caregivers navigate the healthcare system barriers efficiently and effectively at any point along the care continuum, improving patient care at all levels of an organization. Objectives: To synthesize the best available evidence on the effectiveness of a patient navigator on patient satisfaction in adult patients 18 years and older in ambulatory care settings. Inclusion criteria Types of participants : This review considered studies that involved adults of any ethnicity, race or gender, aged 18 years or older, regardless of diagnoses, stage of illness, whether the illness is acute or chronic or previous treatment, who had been receiving care in an ambulatory care setting. Types of intervention(s)/phenomena of interest : This review considered studies on the use of a patient navigator as an additional intervention to usual care for promoting patient satisfaction for adult patients in an ambulatory care setting. Usual care without a patient navigator was considered as a comparator. Types of studies : This review considered experimental and observational studies. Outcomes : The outcome considered was patient satisfaction. Search strategy: The literature search included published and unpublished studies in the English Language from 1990 through July 2015. A search of PubMed, CINAHL, Excerpta Medica Database (EMBASE), Academic Search Premier, Cochrane Library, PsycINFO and Health Source: Nursing/Academic Edition, Social Work Abstracts and Web of Science was conducted. A search for gray literature and electronic hand searching of relevant journals was also performed. Methodological quality: Two reviewers independently evaluated the included studies for methodological quality utilizing standardized critical appraisal instruments from the Joanna Briggs Institute. Data extraction: Standardized data extraction tools from Joanna Briggs Institute were used by two independent reviewers for data extraction. Data synthesis: A statistical meta-analysis was not possible due to heterogeneity between the included studies. Results are presented in a narrative form. Results: Four studies were included in this review, two were randomized controlled trials (RCTs), one was a quasi-experimental pre-post-test design study and one was a cohort study. The four studies showed that a patient navigator had clinical benefit for patient satisfaction, care coordination and patient access to timely healthcare services. One RCT reported a mean satisfaction score of 4.3 for navigated patients and 2.9 for non-navigated patients; P < 0.001. A second RCT showed an odds ratio 1.29; 95% confidence interval 0.92-1.82 for navigated versus non-navigated patients. The quasi-experimental pre-test-post-test study showed navigated patient satisfaction with a mean = 11.45 (standard deviation [SD], 3.69) in comparison with the non-navigated patient (mean, 14.95; SD, 1.69) ( F = 11.85; P = 0.000). The cohort study demonstrated a mean satisfaction score of 90.7 for navigated patients and 85.5 for non-navigated patients; P = 0.03. The four studies showed no clinically significant results; however, the patient navigator role may promote relationships among the healthcare team, reducing barriers for patient-centered care and enhanced patient satisfaction. Conclusion: There is a paucity of evidence on the effectiveness of a patient navigator on patient satisfaction. In the four studies selected for inclusion, a patient navigator had a positive effect on patient satisfaction, although none of the studies demonstrated statistical significance with a patient navigator on patient satisfaction. The effect of a patient navigator remains questionable with differences in perceptions on the best individual for the role and the expected role perception and performance. A standardized approach to the role of the patient navigator may maximize health outcomes and positively affect the quality of life for all patients.